Metabolic acidosis post kidney transplantation - Tariq, Hafsa; Dobre, Mirela (Frontiers in Physiology, 2022)
Metabolic acidosis, a common complication in patients with chronic kidney disease (CKD), results in a multitude of deleterious effects. Though the restoration of kidney function following transplantation is generally accompanied by a correction of metabolic acidosis, a subset of transplant recipients remains afflicted by this ailment and its subsequent morbidities. The vulnerability of kidney allografts to metabolic acidosis can be attributed to reasons similar to pathogenesis of acidosis in non-transplant CKD, and to transplant specific causes, including donor related, recipient related, immune mediated factors, and immunosuppressive medications. Correction of metabolic acidosis in kidney transplantation either with alkali therapy or through dietary manipulations may have potential benefits and the results of such clinical trials are eagerly awaited. This review summarizes the published evidence on the pathogenesis and clinical consequences of chronic metabolic acidosis in kidney transplant recipients.